A Geospatial Assessment of Urban Transportation Systems in Ibadan North Local Government Area, Oyo State - Akinpelu, A. A.; Amusa, I. A.; Akindiya, O. M.; Nmeregini, C. S. (Journal of Spatial Information Sciences, 2025)
Urban Transportation contributes immensely to the socio-economic growth of nations including Nigeria and also helps regions and countries to become more prosperous and productive. The study applied GIS in urban transportation planning in Ibadan North Local Government Area of Oyo State to solve problems like traffic congestions, illegal bus-stops and non-availability of digital road maps. GIS technology was used to look into transportation future in Ibadan by expanding the already existing roads and the affected structures were determined. GIS methodology was adopted by using both primary and secondary data sets to design and create spatial database. Handheld GPS was used to coordinate the locations of the bus-stops while the analogue map from Town Planning Office was scanned, georeferenced and the entities digitized using ArcGIS 10.8.1. The study adopted 1000m spacing for bus-stops to get 26 instead of existing 55. The study identified six major routes: Orogun-Mokola (7.31km), Orogun-Agodi-Beere (9.32km), Mokola-Agodi Gate (3.6km), Sango-Polytechnic (2.25km), Beere-Gate Bus Stop (2.80km) and Gate-Basorun (3.74km) with widths between 25.02m and 14.39m. The expansion of these routes will affect 1002 buildings for Bus Rapid Transit. Orogun-Mokola and Mokola-Agodi Gate routes were conceived for rail system. The road corridors if extended to 60m; 358 and 129 buildings will be affected along Orogun-Mokola and Mokola-Agodi Gate routes respectively. The study generated best and alternative routes to be 5.42km and 5.88km respectively between Amusement Park and UCH. The study concluded by recommending consideration for road junctions when citing bus stops and further study on congestion index along the major routes.